Coastal Landfills and Rising Sea Levels: A Challenge for the 21st Century - Nicholls, Robert J.; Beaven, Richard P.; Stringfellow, Anne; Monfort, Daniel; Le Cozannet, Gonéri; Wahl, Thomas; Gebert, Julia; Wadey, Matthew; Arns, Arne; Spencer, Kate L.; Reinhart, Debra; Heimovaara, Timo; et al. (Frontiers in Marine Science, 2021)
Populated coastal areas worldwide have a legacy of numerous solid waste disposal sites. At the same time, mean sea level is rising and likely to accelerate, increasing flooding and/or erosion. There is therefore concern that landfill sites located at and near the coast pose a growing risk to the environment from the potential release of liquid and solid waste materials. This paper aims to assess our present understanding of this issue as well as research and practice needs by synthesizing the available evidence across a set of developed country cases, comprising England, France, Germany, the Netherlands, and the United States (Florida). Common insights gained here include: (1) a lack of data and limited appreciation of waste release from coastal landfill as a potential problem; (2) recognition of the scale and diversity of coastal landfill waste within a range of generic settings (or situations); and (3) a lack of robust protocols that allow the impact of different categories of waste release to the coast to be assessed in a consistent and evidence-based manner, most particularly for solid waste. Hence, a need for greater understanding of the following issues is identified: (1) the amount, character and impact of waste that could be released from landfill sites; (2) the acceptability and regulation of waste eroding from coastal landfills; (3) present and future erosion rates at landfill sites suggesting the need for more monitoring and relevant predictive tools; (4) the full range of possible management methods for dealing with waste release from landfills and the science to support them; and (5) relevant long-term funding mechanisms to address this issue. The main focus and experience of current management practice has been protection/retention, or removal of landfills, with limited consideration of other feasible solutions and how they might be facilitated. Approaches to assess and address solid waste release to the marine/coastal environment represent a particular gap. Lastly, as solid waste will persist indefinitely and sea levels will rise for many centuries, the long timescale of this issue needs wider appreciation and should be included in coastal and waste policy.